The conservation value of habitat remnants for flower visiting insects in the lowlands of the Cape Floristic Region - Vrdoljak, Sven Michael (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD(Agric) (Conservation Ecology and Entomology))--University of Stellenbosch, 2010.